DOCOSAHEXAENOIC ACID PARTIALLY AMELIORATES DEFICITS IN SOCIAL BEHAVIOR AND ULTRASONIC VOCALIZATIONS CAUSED BY PRENATAL ETHANOL EXPOSURE - Wellmann, Kristen A. (Behav Brain Res, 2015)
Prenatal ethanol exposure disrupts social behavior in humans and rodents. One system particularly important for social behavior is the somatosensory system. Prenatal ethanol exposure alters the structure and function of this area. Docosahexaenoic acid (DHA), an omega 3 polyunsaturated fatty acid, is necessary for normal brain development and brains from ethanol-exposed animals are DHA deficient. Thus, we determined whether postnatal DHA supplementation ameliorated behavioral deficits induced by prenatal ethanol exposure. Timed pregnant Long-Evans rats were assigned to one of three groups: ad libitum access to an ethanol-containing liquid diet, pair fed an isocaloric isonutritive non-alcohol liquid diet, or ad libitum access to chow and water. Pups were assigned to one of two postnatal treatment groups; gavaged intragastrically once per day between postnatal day (P)11 and P20 with DHA (10 g/kg in artificial rat milk) or artificial rat milk. A third group was left untreated. Isolation-induced ultrasonic vocalizations (iUSVs) were recorded on P14. Social behavior and play-induced USVs were tested on P28 or P42. Somatosensory performance was tested with a gap crossing test around P33 or on P42. Anxiety was tested on elevated plus maze around P35. Animals exposed to ethanol prenatally vocalized less, play fought less, and crossed a significantly shorter gap than control-treated animals. Administration of DHA ameliorated these ethanol-induced deficits such that the ethanol-exposed animals given DHA were no longer significantly different to control-treated animals. Thus, DHA administration may have therapeutic value to reverse some of ethanol’s damaging effects.